Laurent Adatto, Enjeux et prospectives du développement des technologies quantiques (Challenges and Prospects in the Development of Quantum Technologies | Wyzwania i perspektywy w rozwoju technologii kwantowych), „ISTE OpenScience” 2023, vol. 23-8, s. 1–15 - Wolska, Hanna; Trela, Anna (Studia Prawa Publicznego, 2025)
Laurent Adatto, Enjeux et prospectives du développement des technologies quantiques (Challenges and Prospects in the Development of Quantum Technologies | Wyzwania i perspektywy w rozwoju technologii kwantowych), „ISTE OpenScience” 2023, vol. 23-8, s. 1–15.